STRATEGI DIGITAL MARKETING SEBAGAI PEMBANGKIT DAYA SAING UMKM DESA UNGGA - I Wayan Joniarta; Sony Januarda; Luluk Hariska; Feby Oktavia; Khairul Amri; Hendrajid Haerul Putra; Riski Hidayah; Hera Rohalia; Juleha Juleha; Salwana Islami; Satya Ulumuna Lestari (Jurusan Teknik Elektro Universitas Mataram, 2026)
Community service is a crucial instrument for significant social change at the local level. Micro, Small, and Medium Enterprises (MSMEs) in Ungga Village have significant potential in the weaving and silver crafts sectors, but still face conventional marketing constraints and low digital literacy. This activity aims to increase MSMEs' understanding of digital marketing as a strategy for market expansion. The method used in this activity is counseling and outreach, using a qualitative, descriptive, participatory approach through observation, interviews, and outreach. The activities included material delivery, interactive discussions, and an introduction to websites as a promotional flatforms. The results of this community service activity were very inspiring in aligning practical activities with theoretical concepts, demonstrating an increased understanding of the partners regarding the importance of branding, visual identity, and the use of digital media for product marketing. This outreach provided initial preparation for MSMEs to develop sustainable digital-based marketing strategies to increase business competitiveness.